Utilization of Agricultural Waste into Organic Fertilizer in Gelebak Dalam Village in Banyuasin Regency - Marlina, Neni; Aryani, Ida; Kalasari, Rastuti; Khodijah, Khodijah; Marlina, Marlina; Asmawati, Asmawati; Purwanti, Yani; Nunilahwati, Haperidah; Meidelima, Dewi; Astuti, Dessy Tri; Rosmiah, Rosmiah; Aminah, Iin Siti; Lusia, Maria; Husna, Nurul; Aluyah, Cik (Altifani Journal: International Journal of Community Engagement, 2022)
The community of Gelebak Dalam Village, Rambutan Sub-district, Banyuasin Regency is a village rich in plants and livestock, including rice, vegetables and fruits as well as chickens, cows, goats, ducks. All of them are sources of agricultural waste that can be used as organic fertilizer. The processed organic fertilizers can be used for rice, vegetables and fruit crops, reduce organic agricultural agricultural waste which can improve land to become more fertile and quality in the resulting production (improve the quality in terms of taste) and can very clearly reduce the use of chemical fertilizers. This counseling was carried out from July 2022 to August 2022 for the people of Gelebak Dalam Village The methods used included counseling, demonstration of making organic fertilizers and mentoring until organic fertilizers were successfully made. The aim of this counseling is that it is hoped that the community can utilize agricultural waste to be processed into organic fertilizer. The hope that the Village community will process agricultural waste into organic fertilizer is very large with successive questions arising and will enthusiastically try to apply it to their own rice fields and gardens. The results achieved are that farmers have succeeded in making organic fertilizer from agricultural waste in the village of Gelebak Dalam.